Mindfulness-Based Counseling as an Experiential Approach to Reducing Student Stress: A Qualitative Study in School Settings - Rianti, Yesi (Journal of Therapia, 2025)
Academic stress among students has intensified due to increasing academic demands, continuous evaluation, and social pressures within school environments. Mindfulness-based counseling has emerged as an alternative approach to stress management in schools; however, its effectiveness is predominantly assessed through quantitative outcome measures, offering limited insight into students’ lived experiences. This study aims to explore how students experience and make meaning of mindfulness-based counseling in relation to academic stress, identify factors influencing its perceived effectiveness, and examine its implications for school counseling practice. Employing a qualitative phenomenological design, this study involved in-depth semi-structured interviews with junior and senior high school students who participated in mindfulness-based counseling programs. Data were analyzed using interpretative thematic analysis to capture patterns of meaning and experiential change. The findings indicate that mindfulness-based counseling facilitates a shift in students’ awareness of thoughts and emotions, supports emotional acceptance, and transforms impulsive stress responses into more reflective and regulated reactions. The effectiveness of mindfulness-based counseling was found to be strongly influenced by relational quality with counselors, school climate, and structural conditions such as time allocation and academic workload. This study concludes that mindfulness-based counseling contributes to stress reduction primarily through experiential transformation rather than symptom elimination. Integrating students’ subjective perspectives is essential for developing context-sensitive and sustainable mindfulness practices in school counseling.